Tabel Partisi Pada STARS: Konsep Dan Evaluasi (Studi Kasus STARS UKSW) - Boymau, Infraim Oktofianus; Tanaem, Penidas Fiodinggo; Tanaamah, Andeka Rocky (Jurnal Informatika: Jurnal Pengembangan IT, 2023)
Database performance is one of the main components in supporting the sustainability of a system, in this case, STARS. In the system context, data will usually be collected into a database. Tied to the data collection process, this really affects the performance of a system as a whole, in this case when executing a query to get a return of the execution results, because the performance of the database itself will be affected by the amount of data available. One way to improve the performance of the database is to use the partition table concept. Thus, in this research a design and evaluation of the partition table will be carried out which will then be applied to the SWCU STARS database. This research focuses more on the use of vertical partitions and list partitions by utilizing PostgreSQL version 14. The stages used in this study. These stages include data collection, partition design, technical partition, testing and implementation. The results of this study indicate that partition tables have better performance than non-partition tables. Judging from some of the sql syntax, namely update, delete and select, while insert has poor performance for partition tables compared to non-partition tables